Can Pediatric Appendicitis Risk Calculator Replace Pediatric Appendicitis Score? A Comparative Study in Diagnosing Acute Appendicitis in Children - Egha; Windi Astriana; Theodorus (Surgery Department, Faculty of Medicine Universitas Sriwijaya, 2025)
Introduction: Acute appendicitis is the most common cause of operative emergencies in children, necessitating prompt and accurate diagnosis to minimize complications. Clinical scoring systems like the pediatric appendicitis score (PAS) and the more recent pediatric appendicitis risk calculator (pARC) have been developed to aid in diagnosis. This study aimed to compare the accuracy of pARC and PAS in diagnosing acute appendicitis in children. Methods: This retrospective study analyzed the medical records of pediatric patients (age: 5-18 years) admitted to Dr. Mohammad Hoesin General Hospital Palembang with suspected acute appendicitis between October 2022 and October 2024. pARC and PAS scores were calculated for each patient, and their diagnostic accuracy was compared using histopathology results as the gold standard. Sensitivity, specificity, positive predictive value (PPV), negative predictive value (NPV), and kappa statistics were calculated. Results: A total of 36 patients with histopathologically confirmed acute appendicitis were included. The pARC score demonstrated a sensitivity of 82.8%, specificity of 100%, PPV of 96.6%, and NPV of 100%. The PAS score showed a sensitivity of 80.0%, specificity of 100%, PPV of 96.5%, and NPV of 100%. The kappa statistic indicated good agreement between pARC and PAS (0.861). Conclusion: Both pARC and PAS demonstrated high accuracy in diagnosing acute appendicitis in children. While pARC showed slightly higher sensitivity and PPV, the difference was not statistically significant. These findings suggest that pARC could potentially replace PAS as the preferred diagnostic tool, but further research with larger sample sizes is needed to confirm these results.